IMPLEMENTATION OF INTERNATIONAL COMMUNICATION STANDARDS IN THE COMMUNICATION SYSTEM OF FERGANA REGION: HISTORICAL EXPERIENCE AND RESULTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article chronologically analyzes the historical processes, stages, and results of integrating international communication standards into the communication network of the Fergana region from the late XIX to the early XXI centuries. The research examines the transition from traditional postal and telegraph services to modern telecommunication systems, focusing on how global technological standards were adapted to the regional infrastructure. Based on archival documents and historical facts, the paper highlights the socio-economic impacts of these technological upgrades, the role of international norms in modernizing the regional communication network, and the integration of the Fergana Valley into the global information space during the years of Independence.